Mechanism of Faster CH4 Bubble Growth Under Surface Waves in Muddy Aquatic Sediments: Effects of Wave Amplitude, Period, and Water Depth - Painuly, Abhishek; Katsman, Regina (Frontiers in Earth Science, 2022)
Methane (CH4) transport from organic-rich fine-grained shallow aquatic (muddy) sediments to water column is mediated dominantly by discrete bubbles, which is an important natural source of greenhouse CH4. Lifespan of these bubbles within sediment constitutes two successive stages: growth from nucleation up to mature size and its buoyant ascent towards sediment - water interface. Bubbles often experience oscillating overburden load due to passage of winds/storm induced short period surface waves or long period tides, which can potentially affect both stages of bubble’s lifespan. However, little is known about the wave effects over bubble growth phase. In present work this subject is investigated using a numerical single-bubble mechanical/reaction–transport model, and the effects of different parameters of the wave loading (amplitude and period) and of the water depth, over the bubble growth pattern and its specific characteristics in sediments, is quantified. It was found that bubbles induce early sediment fracturing in presence of waves, attributed to low overburden load appearing at wave troughs. Bubbles in shallow depth rapidly grow at wave troughs by inducing multiple intense fracturing events, however, this ability decrease with an increasing water depth (because of a slower solute influx). In presence of waves, bubbles mature in lesser time, whose contrast from the no wave case is controlled by the ratio of wave amplitude to equilibrium water depth. Due to higher frequency of occurrence of wave troughs for shorter-period waves, they accelerate the bubble growth more compared to the long-period waves. Overall, conducted modelling suggests that fastest bubble growth can be predicted under higher amplitude short period waves travelling in shallow water. We further infer that accelerated bubble growth, along with subsequent wave induced ascent can sufficiently shorten the bubble’s total lifespan in sediment, which explains the observed episodic in-situ ebullitions correlated with wind- or storm-induced waves.